Nominal Performance of Future Dual Frequency Dual Constellation GBAS - Daniel Gerbeth; Mihaela-Simona Circiu; Maria Caamano; Michael Felux (International Journal of Aerospace Engineering, 2016)
In this work an overview of numerous possible processing modes in future dual frequency, dual constellation GBAS is given and compared to the current GAST D standard. We discuss the individual error contributions to GBAS protection levels and give an overview of the general processing. Based on this the consequences when adding a second constellation as well as frequency are investigated. Geometrical implications and changes to the residual differential error bounds are studied separately first. In terms of geometry a comparison between the single and dual constellation case is presented using dilution of precision as metric. The influence on the different sigma contributions when using new satellites (Galileo) and signals (E1, L5, and E5a) is individually discussed based on recent measurements. Final simulations for different varying parameters are carried out to compare relevant processing modes in terms of achieved nominal protection levels. A concluding discussion compares the outcomes and analyzes the implications of choosing one or the other mode.